2002
DOI: 10.1034/j.1600-0404.2002.1o040.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial and environmental risk factors in Parkinson's disease: a case-control study in north-east Italy

Abstract: We conclude that both familial and environmental factors may contribute to PD aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
5
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 25 publications
7
111
5
2
Order By: Relevance
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
See 4 more Smart Citations
“…A similar Danish study also reported a weak association (standardized hospitalization ratio, SHR, 1.30, 95% CI 1.03-1.63) [354]. Among 29 case-control studies that studied rural living as an exposure, 11 reported an increased risk of PD [136,141,142,147,153,289,293,303,305,309,314] with ORs ranging between 1.5 and 4.9. One study reported an inverse association [350], whereas the others found no association [131, 143-146, 154, 291, 307, 311, 312, 315, 316, 321, 325, 356-358].…”
Section: Farming Rural Living Well Water Usementioning
confidence: 88%
“…Although familial aggregation has been investigated in a large number of studies, most of them were hospital-based . The relative risk (RR) of PD when having a firstdegree relative with PD compared to having no first-degree relative with PD in these studies ranged between 1.6 and 10.4, although one study reported an odds ratio (OR) of 41.7 [147]. In general, population-based studies [155][156][157][158][159][160][161][162][163] reported lower RRs, with a range between 1.5 and 7.5.…”
Section: Family Studiesmentioning
confidence: 96%
See 3 more Smart Citations